2008
DOI: 10.1088/1475-7516/2008/11/010
|View full text |Cite
|
Sign up to set email alerts
|

Stable and ‘bounded excursion’ gravastars, and black holes in Einstein’s theory of gravity

Abstract: Dynamical models of prototype gravastars are constructed and studied. The models are the Visser-Wiltshire three-layer gravastars, in which an infinitely thin spherical shell of a perfect fluid with the equation of state p = (1 − γ)σ divides the whole spacetime into two regions, where the internal region is de Sitter, and the external is Schwarzschild. When γ < 1 and Λ = 0, it is found that in some cases the models represent stable gravastars, and in some cases they represent "bounded excursion" stable gravasta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 20 publications
1
51
0
Order By: Relevance
“…(11), (12), (18) and (19) one can get the following relation between the metric potentials ν and λ as…”
Section: The Field Equations and Their Solutions In F (R T ) Grmentioning
confidence: 99%
See 1 more Smart Citation
“…(11), (12), (18) and (19) one can get the following relation between the metric potentials ν and λ as…”
Section: The Field Equations and Their Solutions In F (R T ) Grmentioning
confidence: 99%
“…However, these works are mainly carried out by several authors in the framework of Einstein's general relativity [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Though it is well known that Einstein's general relativity is a unique tool for uncovering many hidden mysteries of Nature, yet some observational evidences of the accelerating universe along with the existence of dark matter has imposed a theoretical challenge to this theory [20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Lately, we studied both types of gravastars [7][8][9][10][11], and found that, such configurations can indeed be constructed, although the region for the formation of them is very small in comparison to that of black holes.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the discussions about the gravastar picture some authors have proposed alternative models [59][60][61][62][63]. Among them, we can find a Chaplygin dark star [64], a gravastar supported by non-linear electrodynamics [65], a gravastar with continuous anisotropic pressure [66].…”
mentioning
confidence: 99%